Case Report: Differential lung ventilation with jet ventilation via a bronchial blocker for a patient with a large thoracogastric airway fistula after esophagectomy - Wu, Wenqi; Li, Sibei; Song, Xiuling; Wang, Xia; Wang, Yong; Cai, Chengyi; Wang, Jiyong; Li, Yuhui; Ma, Wuhua (Frontiers in Surgery, 2022)
Background: Thoracogastric airway fistula (TGAF) is a rare and potentially fatal complication of esophagectomy for esophageal and cardiac carcinomas. Isolation of the fistula and pulmonary separation is necessary to during the surgical repair of TGAF. However, the prevailing airway management options for trachesophageal fistula repair reported so far is not applicable to patients with large TGAF. This case presents an alternative technique for performing differential lung ventilation in a patient with thoracogastric airway fistula. Case presentation: A 70-year-old male was diagnosed with thoracogastric airway fistula situated above carina after esophagectomy, and thoracoscope-assisted repair of the fistula was scheduled. Due to aspiration pneumonia and the size (3.5cm × 1.7cm) of the fistula, patients cannot tolerate one-lung ventilation and complex intubating operation. We therefore performed differential lung ventilation by a combination of the left bronchial intubation and a bronchial blocker in the right main bronchus. An extended 6.5#single-lumen endotracheal tube was inserted into left main bronchus and a 9# bronchial blocker was placed in right main bronchus with the aid of a fiberscope. The right lung was selectively inflated with jet ventilation, while positive pressure ventilation was maintained through the left endotracheal tube. The value of SPO2 remained above 95% throughout the operation. Conclusion: For patients with a large thoracogastric airway fistula, differential lung ventilation of a combination of positive pressure ventilation and jet ventilation is useful. Inserting an extended single-lumen endotracheal tube into the left main bronchus and a bronchial blocker in the right main bronchus could be another way of providing differential ventilation for patients with thoracogastric airway fistula.